Effects of cerium on structures and electrical properties of (Nb, Ta) modified Bi4Ti3O12 piezoelectric ceramics. Issue 6 (21st February 2022) - Zhang, Feifei; Xu, Yugen; Yang, Heng; Guan, Shangyi; Shi, Wei; Chen, Yulin; Huang, Chenting; Xing, Jie; Liu, Hong; Chen, Qiang
Abstract: Bi4 Ti3 O12 high‐temperature piezoelectric ceramics composed of 0.03 mol (Nb, Ta) 5+ substituting B site and x mol CeO2 ( x  = 0–0.05, abbreviated as BCTNT100 x ) substituting A site were synthesized by the conventional solid‐state reaction method. The effects of Ce additive on the structures and electrical properties of resulting Bi4 Ti3 O12 ‐based ceramics were systematically investigated. In‐situ temperature‐dependent X‐ray diffraction (XRD) confirmed that the phase structure of BCTNT100 x ceramics change from orthorhombic structure to tetragonal structure as temperature increased. The ceramics at Ce content x  = 0.03 illustrated optimal performances with superior piezoelectric constant ( d 33  = 36.5 pC/N), high Curie temperature ( T C  = 649 °C), and large remanent polarization (2 P r  = 21.6 μC/cm 2 ). BCTNT3 ceramics also possessed high d 33 of 32.5 pC/N at an annealing temperature of 600°C, with electrical resistivity preserved at 10 6 Ω cm at 500 °C. These results demonstrate that BCTNT100 x ceramics can be used as high‐temperature piezoelectric devices.